The level of interleukin-6, serum calprotectin, and hypersensitive C-reactive protein in Crohn’s disease-related mucosal damage: Serum calprotectin, hypersensitive CRP, and interleukin-6 in gut mucosal damage - Zhang, Chuanshuo; Zhou, Fengning; Cao, Xiandong; Qiu, Chenyang; Lu, Mingdian; Yu, Xin; Xiang, Pingping; Yu, Bo; Zhou, Bo (Journal of Medical Biochemistry, 2025)
[Objective] To evaluate calprotectin, hypersensitive C-reactive protein, and interleukin-6 for detecting digestive tract mucosal injury in Crohn’s disease (CD) patients. [Methods] 52 patients diagnosed with CD were selected. Fecal samples from the patients were collected to detect calprotectin (ELISA), and serum samples were collected to detect hs-CRP (Immunoturbidimetry) and IL-6 (Chemiluminescence). All patients with CD underwent colonoscopy or capsule endoscopy. According to the modified endoscopic severity index of CD (SES-CD). Comparisons were made between the two groups’ variations in calprotectin, hs-CRP, and IL-6 levels, and ROC curves were drawn to analyze the diagnostic efficacy (AUC) of each index and combined detection for mucosal injury. [Results] In the Mucosal injury group, the calprotectin, hs-CRP levels were significantly greater than those in the mucosal healing group. Calprotectin had the highest AUC (0.93, 95% CI: 0.88–0.98), sensitivity (88.5%), and specificity (89.2%) when the critical value was greater than 250μg/g, according to ROC analysis. The AUC of the three indicators’ combined detection (logistic regression model) rose to 0.96, which was noticeably superior than that of a single indicator (P<0.05). [Conclusion] Interleukin-6, serum calprotectin, and hypersensitive C-reactive protein levels are significantly correlated with the degree of mucosal injury in patients with CD. Among them, calprotectin has the best diagnostic value. The combined detection of these three factors can significantly improve the recognition of mucosal injury in the active stage of CD.